Electronic Word of Mouth as A Motivation Tool in Searching, Using Information and Travel Decision: An Empirical Study in Shiraz - Roya Sadat Alavi Pour; Hadi Rafiei Darani; Ali Rahnama (International Journal of Tourism and Hospitality in Asia Pasific, 2020)
This paper conducts an overview of electronic word-of-mouth (eWOM), and will argue about eWOM function to form attitudes about a destination, and purchasing inclinations, and the decision-making process as a whole. Data were collected by an electronic questionnaire. For testing hypothesizes, modeling of structural equations and correlation coefficient, which conducted by AMOS and SPSS is used. The sample is chosen based on three factors. Among hypothesises, three hypotheses are approved. That means the eWOM has noticeable effects on customers’ attitudes and experience. Also, the disapproval of other hypotheses showed that the eWOM effect on the customers’ satisfaction and purchase intentions is low and should be evaluated in the contribution of other factors.